How much have the perinatal outcomes of triplet pregnancies improved over the last two decades? - Kyu-Sang Kyeong; Jae-Yoon Shim; Soo-young Oh; Hye-Sung Won; Pil Ryang Lee; Ahm Kim; Sung-Cheol Yun; Pureun-Narae Kang; Suk-Joo Choi; Cheong-Rae Roh (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveThis study was conducted to demonstrate the temporal trends in perinatal outcomes of triplet pregnancies over the last two decades.MethodsThe medical records of patients with triplet pregnancies at two Korean tertiary-care hospitals from 1992 to 2012 were retrospectively reviewed in regard to maternal and neonatal outcomes. The study was divided into two periods for analysis: period I (1992-2001) and period II (2003-2012).ResultsOver a 21-year period, 65 women with triplet pregnancies and 185 neonates were analyzed. Period II, when compared with period I, was associated with improved maternal outcomes, characterized by a decreased incidence of preeclampsia (31.8% vs. 2.3%, P=0.002) and anemia (68.2% vs. 30.2%, P=0.003) during pregnancy. Regarding neonatal aspects, the composite morbidity of period II was significantly decreased compared with that of period I, as assessed with a generalized estimating equation for logistic regression (26.2% vs. 8.1%, P=0.03). Multivariable analysis revealed that the gestational age at delivery and the period were significantly associated with the composite neonatal morbidity (P<0.001 and 0.007, respectively).ConclusionImproved neonatal morbidity was associated with a higher gestational age at delivery and with the more recent decade.